Adjuvanted versus nonadjuvanted influenza vaccines and risk of hospitalizations for pneumonia and cerebro/cardiovascular events in the elderly - Francesco Lapi; Ettore Marconi; Monica Simonetti; Vincenzo Baldo; Alessandro Rossi; Aurelio Sessa; Claudio Cricelli (Taylor & Francis Group, 2019)
Background: The higher effectiveness of MF59®-adjuvanted trivalent influenza vaccine (MF59-TIV) vs. nonadjuvanted TIV in preventing influenza-related hospitalizations was found considering few influenza seasons, local and heterogeneous settings. This study evaluated the relative vaccine effectiveness (rVE) of MF59-TIV vs. nonadjuvanted TIV on the risk of hospitalization for pneumonia and cerebro/cardiovascular events across 15 consecutive influenza seasons. Research design and methods: Using Health Search Database, a case-control study was nested in a cohort of elderly vaccinated with MF59-TIV or TIV. Conditional logistic regression was used to estimate the odds ratio with 95% confidence intervals (CI) of hospitalizations potentially related to influenza in patients vaccinated with MF59-TIV or TIV. Results: Of 43,000 patients vaccinated with MF59-TIV (66.2%) and TIV (33.8%) for the first time, 103 cases of hospitalization for pneumonia or cerebro/cardiovascular events (0.11 per 1,000 person-weeks) during 15 influenza seasons were identified. The MF59-TIV was associated with a reduced risk of hospitalizations for pneumonia and cerebro/cardiovascular events vs. TIV [rVE: 39% (95% CI: 4-61%)]. Conclusions: In a 15-season cohort of elderly, MF59-TIV seems to reduce the risk of hospitalizations for pneumonia and cerebro/cardiovascular events when compared with nonadjuvanted TIV. Our findings support the recommendation for MF59-TIV in the elderly population.